Spatial Modeling of Vegetation Cover for Soil Erosion Control Based on Arc GIS and the RUSLE Models - Dimas Prabowo Harliando; Chandra Setyawan; Hanggar Ganara Mawandha (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Deforestation in the Serayu watershed, Central Java province, Indonesia for agriculture and other uses leaves only 0.73% of vegetation. It has triggered a number of problems such as soil loss (erosion), landslides, floods and sedimentation downstream. Environmental damage control needs to be applied through appropriate conservation programs. This study aims to understand the distribution of soil erosion and the effectiveness of soil erosion control by using vegetation cover. Soil erosion modeling and its correlation to vegetation cover was performed by using an Arc GIS based model of the Revised Universal Soil Loss Equation (RUSLE) through five scenarios of vegetation landscape cover such as 10%, 15%, 20%, 25%, and 30% of the total area of the study site. Five parameters namely rain erosivity (R), soil erodibility (K), slope-length (LS) and crop management (C) and conservation practices (P) factor were used to calculate soil erosion. The results indicated 82.25 tons/ha/year soil erosion reduction due to enhancement of vegetation cover from the actual condition 0.73% to the 30% vegetation cover condition. The increase of 5% vegetation landscape cover (forest) detracted the soil erosion rate by 10,20 tons /ha/year. Very high and high soil erosion hazard levels were found in the northern, east, and west watershed areasKeywords:   Soil erosion, RUSLE model, GIS, Serayu watershed, Vegetation cover